Perceived Rigidity Significantly Affects Visually Induced Self-Motion Perception (Vection). (May 2019) - Nakamura, Shinji
When an observer sees a uniformly moving visual stimulus, he or she typically perceives an illusory motion of his or her body in the opposite direction (vection). In this study, the effects of the visual inducer's perceived rigidity were examined using a horizontal sine wave-like line stimulus moving horizontally. Lowering the sine wave amplitude resulted in the perception of a less rigid visual stimulus motion, although the stimulus was always set to move completely rigidly. The psychophysical experiment revealed that visual self-motion perception was weaker in the lower amplitude condition where the visual stimulus was perceived as less rigid. The follow-up experiments showed that the effects of sine wave amplitude manipulation were unrelated to the modulation of the perceived speed. Furthermore, small gaps inserted into the sine waves effectively increased the perceived rigidity and resulted in a strong self-motion perception even in the lower amplitude condition. The current investigation, together with previous studies, clearly demonstrated that perceived features, in addition to the physical ones, play a key role in visual self-motion perception. Visual stimuli, perceived as more rigid, provide a more reliable frame of reference in the observers' spatial orientation, determining their self-motion perception.